2015
DOI: 10.3409/fb63_4.279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Extenders for Liquid Storage at 4ºC of Breeding Chinchilla (<I>Chinchilla lanigera</I>) Semen on Sperm DNA Integrity

Abstract: Influence of selected extenders for liquid storage at 4ºC of breeding chinchilla (Chinchilla lanigera) semen on sperm DNA integrity. Folia Biologica (Kraków) 63: 279-287. The influence of two commercial and two laboratory oriented extenders on survival rate and DNA integrity of chinchilla (Chinchilla lanigera) sperm was determined during liquid storage. Semen was collected using an electroejaculator from 6 adult male chinchillas. Ejaculates (n=16) were diluted with extenders to obtain a concentration of 40×10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
(46 reference statements)
1
11
1
Order By: Relevance
“…Loss of motility and viability after preservation was not surprising and was reported for chinchilla semen previously (Carrascosa et al, 2001;Niedbała et al, 2015;Ponce et al, 1998;Ponzio et al, 2007). CASA evaluation used in this study revealed that additionally to the loss of motility, after preservation spermatozoa slowed down and curved their trajectories, which pattern of changes was observed also in other species (Jayaprakash, Patil, Kumar, Majumdar, & Shivaji, 2001;O'Connell, McClure, & Lewis, 2002).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Loss of motility and viability after preservation was not surprising and was reported for chinchilla semen previously (Carrascosa et al, 2001;Niedbała et al, 2015;Ponce et al, 1998;Ponzio et al, 2007). CASA evaluation used in this study revealed that additionally to the loss of motility, after preservation spermatozoa slowed down and curved their trajectories, which pattern of changes was observed also in other species (Jayaprakash, Patil, Kumar, Majumdar, & Shivaji, 2001;O'Connell, McClure, & Lewis, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Semen quality and preservation have been poorly studied in chinchillas, with only several reports exploring this subject (Barnabe et al, 1994;Carrascosa et al, 2001;Niedbała et al, 2015;Ponce et al, 1998;Ponzio, Busso, Ruiz, & Fiol de Cuneo, 2007). By using computerassisted and flow cytometric approach in this study (for the first time for chinchilla epididymal sperm), we have assessed in detail changes in spermatozoa stored at 5°C and cryopreserved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinchilla lanigera is an endangered species in its natural environment (Leal & Franca, ). Chinchillas were brought to Poland in the 1950s, and since that time breeding of these rodents has become an important branch of agriculture (Niedbała et al, ). Chinchillas are also bred by amateurs as pets.…”
Section: Introductionmentioning
confidence: 99%